Catalytic Enantioselective Synthesis of Mariline A and Related Isoindolinones through a Biomimetic Approach. (2nd November 2017) - Min, Chang; Lin, Yingfu; Seidel, Daniel
Abstract: The catalytic enantioselective synthesis of isoindolinones was achieved through the condensation of 2‐acyl‐benzaldehydes and anilines. In the presence of 1 mol % of a chiral phosphoric acid catalyst, reactions reach completion within 10 min and provide products with up to 98 % ee . Anilines with an ortho t ‐butyl group form atropisomeric products, thereby enabling the simultaneous generation of axial and point chirality from two achiral substrates. This method was applied to the first synthesis of mariline A.